Deliberations with Double-Sided Information - Ulrich Doraszelski (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
Two players need to agree to adopt a certain option, otherwise the status quo is maintained. The correct choice depends of an unknown state variable. While both players would like the correct choice to be made, their relative concern with the two types of mistakes may differ and is private information. Each player observes a private signal that is correlated with the state variable. Before reaching the final decision through simultaneous vote, players communicate by expressing a personal non-binding option. We provide a succinct characterization of the equilibria. Although truthful communication may take place in equilibrium, the players' private information about the state of the world is not fully revealed. In fact, the sole role of communication is to provide a means for each player to decide how to vote when her private signal conflicts with her relative concern. Our calculations show that communication increases ex-ante utility. When only one player may speak, we show that their ex-ante utility is independent on who is selected as a speaker even if the quality of information radically differs among players.
Keywords: C78; D72; D82; 330